Interference of sample size on multicollinearity diagnosis in path analysis - Sari, Bruno Giacomini; Dal'Col Lúcio, Alessandro; Olivoto, Tiago; Krysczun, Dionatan Ketzer; Tischler, André Luís; Drebes, Lucas (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the interference of sample size on multicollinearity diagnosis in path analysis. From the analyses of productive traits of cherry tomato, two Pearson correlation matrices were obtained, one with severe multicollinearity and the other with weak multicollinearity. Sixty-six sample sizes were designed, and from the amplitude of the bootstrap confidence interval, it was observed that sample size interfered on multicollinearity diagnosis. When sample size was small, the imprecision of the diagnostic criteria estimates interfered with multicollinearity diagnosis in the matrix with weak multicollinearity.